Stranded Assets in the Transition to a Carbon-Free Economy - Rick van der Ploeg; Armon Rezai (Center for Economic Studies and ifo Institute (CESifo), 2019)
Assets in the fossil fuel industries are at risk of losing market value due to anticipated breakthroughs in renewable technology and governments stepping up climate policies in the light of the Paris commitments to limit global warming to 1.5 or 2 degrees Celsius. Stranded assets arise due to uncertainty about the future timing of these two types of events and substantial intertemporal and intersectoral investment adjustment costs. Stranding of assets mostly affects the 20 biggest oil, gas and coal companies who have been responsible for at least a third of global warming since 1965, but also carbon-intensive industries such as steel, aluminium, cement, plastics and greenhouse horticulture. A disorderly transition to the carbon-free economy will lead to stranded assets and legal claims. Institutional investors should be aware of these financial risks. A broader definition of stranded assets also includes countries reliant on fossil fuel exports and workers with technology-specific skills.
Keywords: E62; F41; G11; O33; Q33; Q34; Q35; Q40; Q54; 330; de-carbonisation; policy tipping; technology; stranded assets